Annihilating difference : the anthropology of genocide - Hinton, Alexander Laban (California series in public anthropology ;, 2002)
This text presents a collection of original essays on genocide. It explores a wide range of cases, including Nazi Germany, Cambodia, Guatemala, Rwanda, and Bosnia.